1989
DOI: 10.1063/1.101912
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation at 421 nm by resonantly enhanced doubling of GaAlAs laser diode array emission

Abstract: The 842-nm diffraction-limited emission from an injection-locked laser diode array was frequency doubled using a monolithic spherical-mirror KNbO3 crystal cavity. Maximum unidirectional external 421 nm power of 24 mW was generated with 167 mW of pump power. Maximum total internal second-harmonic power and conversion efficiency of 64 mW and 45% were obtained. Effects of heating in the crystal are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Thus electronic engineers are concentrating their attention on frequency doubling of the diode laser. Their research has shown that the conversion efficiency of SHG is improved to 14% (24 mW/167 mW) (31). If this diode laser is available as an excitation source for chromatography or electrophoresis detectors, it will become a powerful tool in trace analysis.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Thus electronic engineers are concentrating their attention on frequency doubling of the diode laser. Their research has shown that the conversion efficiency of SHG is improved to 14% (24 mW/167 mW) (31). If this diode laser is available as an excitation source for chromatography or electrophoresis detectors, it will become a powerful tool in trace analysis.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Short-wavelength operation of laser-diode-pumped solid-state laser systems could be achieved by using nonlinear techniques. Thus, harmonic generation in nonlinear crystals [4] and frequency upconversion [5,6] are two promising techniques. In upconversion laser schemes, excitation of high-energy optical states is achieved either by sequential absorption of pump photons in one ion, or by cooperative transfer involving two or more excited ions, or, as shown recently, by photon avalanche, i.e., a process that involves cross relaxation to populate the metastable states of two ions followed by excited-state absorption (ESA) from these states [7].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high efficiency of frequency doubling, resonant enhancement of the IR light 9 and the high nonlinearity of a KNbO 3 crystal ͑a cut͒ in a semimonolithic resonator configuration are used. 10 ͑AR͒ coated for the fundamental and second harmonic, while the other end face is curved ͑radius rϭ5 mm͒ and highly reflective for both wavelengths. This end face, together with the curved coupling mirror ͑rϭ25 mm, AR at 428 nm, reflectivity Rϭ95% at 856 nm͒, forms the resonator with an optical length of 41.6 mm and a pump waist of 13 m located inside the crystal.…”
mentioning
confidence: 99%